KAJIAN WAKTU TEMPUH PERGERAKAN PENUMPANG DAN BAGASI DI TERMINAL KEDATANGAN BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Sabur, Fatmawati; Jinca, Yamin; Lawi, Armin (Jurnal Transportasi, 2013)
The purpose of this study was to determine differences in travel time and the factors that influence the differences in travel time of passengers and baggage movement in arrival terminal at Sultan Hasanuddin International Airport, Makassar. This research is a correlation study, using primary data from direct measurements in the field as well as secondary data derived from monthly reports of the Divisi Operasional Aeronautical Information Service, which is a fixed flight schedule, and from the Divisi Sisi Udara, in the form of data movement on the apron. Processing data in this study used the SPSS software. The analysis showed the smallest time difference between passengers and baggage occurs when using the bus, followed by the use of aviobridge. The greatest difference in time occurs when walking. It can be concluded that the use of the bus is more effective in reducing delays in baggage reception at the arrival terminal.Keywords: travel time, airport, ground handling, arrival terminal